Innovation of Buddhist Knowledge Diffusion for the development of Thai Societies towards Sufficiency Economy of E-san local scholars. - pariyatidhammawong, Phrakhru; Klinngam, Sanor; Yoophum, Nipapat; Charoenkusol, Thada; Nuekkrathok, Praphan; Thangtong, Worapol; Tongyam, Terdsak (Journal of International Buddhist Studies, 2017)
The purpose of this research was aimed to study the status, role of knowledge, concepts and innovative of Buddhist Knowledge diffusion for the development of Thai societies, towards Sufficiency Economy of E-san local scholars. It was a qualitative method and quantitative method namely by the result of 11 editions of National Economic and Social Development Plan which were compared to the change from sampling behaviors. The aims to study the process of the farmers’ development were based on the Buddhist way and implementation through Sufficiency Economy Philosophy. The research studied how the results of sustainability would be different from each other. In this research, it revealed that the needs for the development of sampling and the response of the development factors were balanced through the examination of the effects on economy, education, faith, confidence, social participation, and quality of life. The Dhamma principles connected with Buddhist economics had to be modified for the sampling’ success, while the communication based on Buddhism and became a point of balance, causing the farmers to modify or change their behaviors in the direction that caused intellectual and lasting happiness towards the development of Sufficiency Economy Philosophy. Moderation was applied to the theory of production; the marketing and consumption from mainstream economic effects were directed by Buddhist economics and Buddhist principles of the Middle Path (Majjhimāpaṭipadā), Noble Eightfold Path (Aṭṭhañgika magga), Threefold Training (Trisikkhã), Chain of Causation (Paṭiccasamuppāda), Seven Qualities of a Good Man (Sappurisadhamma), Five Precepts (Pañcasila) and Five Dharma (Pañcadhama). The Reasonability was regulated by thorough Contemplation (Yonisomanasikāra), Three Characteristics (Tilakkhaña), Fourfold Noble Truths (Catu-Ariyasacca), Four Principles of Success (Catu-Iddhipāda), Four Principles of Social Integration (Catu-Sangahavatthu) and Four Principles of Virtuous Existence (Catu-Brabmavihāra). Self -Immunity Supervised by Mindfulness (Sati-Appamādadhamma) and True Good Friends (Kalyāṇamittatadhamma) in a strong base on knowledge and the morality condition were controlled by the people of knowledge (Bahusutta), Six Channels of Sense (Ãyatanas) that were controlled by the moral shame (Hiri) and the fear to the sin against the corruption (Ottappa)as a starting point. In conclusion, social development strategies of E-san local scholars emphasized on the person’s quality development, person’s cooperative, integration of local and modern wisdom, promoted the local and own reliance and using a member network as an instrument to precede the project. Therefore, the innovative model in this research could also be used in different countries which were of different economics, societies, environments and cultures, because of the synthesis of the natural principles.